Enterprise Risk Management and Corporate Governance Strategic: Emerging Firm Value - et al., Shaliza Alwi (International Journal of Advanced Science and Technology, 2019)
As of late, a change in outlook has happened with respect to the way organizations view risk management. The pattern now is to take a holistic view of risk management instead of looking at it from a silo-based perspective. An enterprise risk management (ERM) is commonly referred as holistic approach toward managing an organization’s risk. For decades, risk management has been a fundamental focus for top managements, particularly in multinationals. Given the benefit of creating greater awareness on the risks potentially faced by the firm, the proponents of enterprise risk management (ERM) also allows for decision-makers to gauge the firm’s ability and resilience towards such risks and subsequently enables the formulation of strategies to mitigate such issues. In today’s dynamic global environment, the importance of enterprise risk management has accelerated and expanded to include enterprise of all forms and sizes.